Big theories revisited. 2 - Liem, Gregory Arief D.; McInerney, D. M. 1948- (Research on sociocultural influences on motivation and learning., 2018)
Students' school motivation and engagement are key contributors to the quality of their academic learning and performance, as well as growth in other important areas of life (social, emotional, and physical health). Fostering motivation and engagement is thus a meaningful educational purpose, both in and of itself and as a pathway to holistic student development. However, motivation and engagement do not develop in a vacuum, and effort seeking to facilitate them cannot be effectively pursued without understanding their underpinning sociocultural influences. In the first edition of this volume, "Big Theories Revisited" (McInerney & Van Etten, 2004), authors of major models of school motivation and engagement were 'challenged' to look into their theoretical work through a sociocultural lens. The volume has been well received as objectively reflected in the number of citations of its chapters.Significant progress has since been made in the theorizing and research of 'big theories' of school motivation and engagement. In this volume, we invited a group of internationally-renowned scholars to re-examine their theoretical and conceptual work by highlighting the 'what' (factors) and 'how' (processes) of sociocultural influences in association with the key motivation and/or engagement construct(s) of their expertise. We made it clear to our contributors that we solicited new chapters rather than chapters with merely rehashed materials. As a result, this volume, "Big Theories Revisited 2" (Liem & McInerney, 2018) contains chapters that critically discuss sociocultural influences on school motivation and engagement constructs as viewed from focal theories including self-determination theory, achievement goal theory, personal investment theory, expectancy value theory, self-efficacy theory, self- and co-regulated learning models, and many others. Whereas some of the chapter topics covered in the initial edition are also part of this edition, some are new and provide fresh sociocultural angles on achievement-relevant processes and outcomes. Likewise, whereas some of the authors contributed to the earlier edition of the Volume, many of them are different. What appears to be the same across the two editions is the scholarly distinction of the authors and the substantive rigor of the chapters in advancing our current understanding of this field of enquiry. Readers will learn much from and be inspired by stimulating ideas presented in this volume.